Duplicity among the dark triad Three faces of deceit. - Jones, Daniel N.; Paulhus, Delroy
Although all 3 of the Dark Triad members are predisposed to engage in exploitative interpersonal behavior, their motivations and tactics vary. Here we explore their distinctive dynamics with 5 behavioral studies of dishonesty (total N = 1,750). All 3 traits predicted cheating on a coin-flipping task when there was little risk of being caught (Study 1). Only psychopathy predicted cheating when punishment was a serious risk (Study 2). Machiavellian individuals also cheated under high risk?but only if they were ego-depleted (Study 3). Both psychopathy and Machiavellianism predicted cheating when it required an intentional lie (Study 4). Finally, those high in narcissism showed the highest levels of self-deceptive bias (Study 5). In sum, duplicitous behavior is far from uniform across the Dark Triad members. The frequency and nature of their dishonesty is moderated by 3 contextual factors: level of risk, ego depletion, and target of deception. This evidence for distinctive forms of duplicity helps clarify differences among the Dark Triad members as well as illuminating different shades of dishonesty.